Integrating pharmacological evaluation and computational identification for deciphering the action mechanism of Yunpi-Huoxue-Sanjie formula alleviates diabetic cardiomyopathy - Zhang, Xin; You, Li-Yan; Zhang, Ze-Yu; Jiang, Dong-Xiao; Qiu, Yu; Ruan, Ye-Ping; Mao, Zhu-Jun (Frontiers in Pharmacology, 2022)
Background: Yunpi-Huoxue-Sanjie (YP-SJ) formula is a Chinese herbal formula with unique advantages for the treatment of diabetic cardiovascular complications, such as Diabetic cardiomyopathy (DCM). However, potential targets and molecular mechanisms remain unclear. Therefore, our research was designed to evaluate rat myocardial morphology, fat metabolism and oxidative stress to verify myocardial protective effect of YP-SJ formula in vivo. And then to explore and validate its probable mechanism through network pharmacology and experiments in vitro and in vivo. Methods: In this study, DCM rats were randomly divided into five groups: control group, model group, and three YP-SJ formula groups (low-dose, middle-dose, and high-dose groups). Experimental rats were treated with 6g/kg/d, 12g/kg/d and 24g/kg/d YP-SJ formula by gavage for 10 weeks, respectively. Cardiac function of rats was measured by high-resolution small-animal imaging system. The cells were divided into control group, high glucose group, high glucose + control serum group, high glucose + dosed serum group, high glucose + NC-siRNA group, high glucose+siRNA-FoxO1 group. The extent of autophagy was measured by flow cytometry, immunofluorescence, and western blotting. Results: It was found that YP-SJ formula could effectively improve cardiac systolic function in DCM rats. We identified 46 major candidate YP-SJ formula targets that are closely related to the progression of DCM. Enrichment analysis revealed key targets of YP-SJ formula related to environmental information processing, organic systems, and the metabolic occurrence of reactive oxygen species. Meanwhile, we verified that YP-SJ formula can increase the expression of forkhead box protein O1 (FoxO1), autophagy-related protein 7 (Atg7), Beclin 1, and light chain 3 (LC3), and decrease the expression of phosphorylated FoxO1 in vitro and in vivo. The results showed that YP-SJ formula could activate the FoxO1 signaling pathway associated with DCM rats. Further experiments showed that YP-SJ formula could improve cardiac function by regulating autophagy. Conclusion: YP-SJ formula treats DCM by modulating targets that play a key role in autophagy, improving myocardial function through a multi-component, multi-level, multi-target, multi-pathway, and multi-mechanism approach.